Pengembangan Media Pembelajaran Game Kuis Edukasi â€œ Who Wants To Be A Miilionaireâ€ Untuk Meningkatkan Hasil Belajar Siswa Pada Mata pelajara PPKN Di Kelas VIII SMP N 18 Kota Jambi - Sutja, Akmal; Iqbal Rizki Ramadhan, Muhammad (Citizenship Education, Faculty of Education, Jambi University, 2023)
This research was motivated by the existence of problems at SMP Negeri 18 Jambi City, namely low student learning outcomes in class VIII B SMP 18 Jambi City, namely 18 students from 32 students who did not complete the odd semester final test or in the sense that 60% of students did not complete and only 40% at KKM 70 in SMP N 18 Kota Jambi subjects who completed class VIII SMP N 18 Jambi City, lack of teacher creativity in processing interesting learning media that prioritizes digitalization. to develop learning media for the educational game â€œwho wants to be a millionaireâ€ in the Civics subject matter of national awakening and to increase student learning outcomes in Civics learning in class VIII B SMP N 18 Jambi City. This research is a research and development (Research and Development) with the ADDIE method (Analysis, design, development, implementation, evaluation). The instruments used in this study were a questionnaire on the validity of material experts, media experts and linguists, responses from subject teachers and learning outcomes tests. The results obtained a score of 77% on the validity test of material experts, a score of 88% on the validity test of media experts and a score of 83% on the validity of linguists with that it can be said that the media is feasible to be tested on class VIII B students of SMP 18 Jambi City. Then at the implementation stage, a score of 96% was obtained for the assessment of subject teachers, a score of 90% for small group student responses and a score of 93% for student responses in large group trials and then 91% of students completed or in the sense that 29 students exceeded the KKM what was determined was 70 of the total number of class VIII B students, namely 32, while only 3 students did not complete, there was an increase in student learning outcomes that previously on the results of student learning tests in the previous semester exams only 40% of students who completed 32 students or only 11 students who completed. Then it was concluded that the educational game product